LINGUO-COGNITIVE FEATURES OF THE TIME CONCEPT IN ENGLISH INTERNET DISCOURSE: AN AI-BASED ANALYSIS - Sapaeva Sokhiba Otakhonovna (International Journal of Literature and Language Studies, 2026)
The rapid development of digital technologies has significantly transformed communication practices and the representation of conceptual categories in online environments. Among these categories, the concept of TIME occupies a central position due to its cognitive, linguistic, and cultural significance. This study investigates the linguo-cognitive features of the TIME concept in English-language internet discourse using artificial intelligence (AI)-assisted analytical methods. The research aims to identify the linguistic means, conceptual metaphors, semantic patterns, and pragmatic functions through which temporal meanings are expressed in contemporary digital communication. The empirical data consist of a corpus of English-language online texts, including social media posts, blogs, news articles, and discussion forum contributions. The study combines discourse analysis, corpus-linguistic methods, conceptual metaphor analysis, and AI-supported semantic clustering. The findings reveal that the TIME concept is predominantly represented through metaphorical models such as TIME IS MONEY, TIME IS A RESOURCE, and TIME IS MOTION. The analysis also demonstrates a strong orientation toward present and future temporal perspectives, reflecting the accelerated nature of digital communication. Furthermore, temporal expressions are closely associated with productivity, efficiency, urgency, and immediacy. The application of AI-assisted methods enabled the identification of recurring semantic patterns and hidden conceptual relationships within the corpus. The results highlight the interaction between language, cognition, and digital culture and demonstrate the value of artificial intelligence as a tool for contemporary discourse studies. The study contributes to research in cognitive linguistics, internet discourse, and AI-assisted linguistic analysis.